Specialized care for people with AIDS in the state of Ceara, Brazil - Pedrosa, Nathália Lima; Santos, Vanessa da Frota; Paiva, Simone de Sousa; Galvão, Marli Teresinha Gimeniz; Almeida, Rosa Lívia Freitas de; Kerr, Ligia Regina Franco Sansigolo (Revista de Saúde Pública, 2015)
OBJECTIVE To analyze if the distribution of specialized care services for HIV/AIDS is associated with AIDS rates. METHODS Ecological study, for which the distribution of 10 specialized care services in the Ceara state, Northeastern Brazil, was obtained, and the mean rates of the disease were estimated per mesoregion. We evaluated 7,896 individuals who had been diagnosed with AIDS, were aged 13 years or older, lived in Ceara, and had been informed of their condition between 2001 and 2011. Maps were constructed to verify the relationship between the distribution of AIDS cases and institutionalized support networks in the 2001-2006 and 2007-2011 periods. BoxMap and LisaMap were used for data analysis. The Voronoi diagram was applied for the distribution of the studied services. RESULTS Specialized care services concentrated in AIDS clusters in the metropolitan area. The Noroeste Cearense and west of the Sertoes Cearenses had high AIDS rates, but a low number of specialized care services over time. Two of these services were implemented where clusters of the disease exist in the second period. The application of the Voronoi diagram showed that the specialized care services located outside the metropolitan area covered a large territory. We identified one polygon that had no services. CONCLUSIONS The scenario of AIDS cases spread away from major urban areas demands the creation of social support services in areas other than the capital and the metropolitan area of the state; this can reduce access barriers to these institutions. It is necessary to create specialized care services for HIV/AIDS in the Noroeste Cearense and north of Jaguaribe.